RESEARCH ON MULTI-BODY DYNAMIC SIMULATION OF HUMANOID FOOT TYPE STAIR CLIMBING WHEELCHAIR BASED ON ADAMS - ZHU Hua; YANG Hui; HUANG ZhenLi; GUO ChangJian; YU YiPeng (Jixie qiangdu)
Based on the design of the new type of humanoid foot shaped wheelchair and the usage of large-scale engineering software named ADMAS,to simplify the wheelchair model to establish a multi-body dynamics system,and analyzed a virtual prototype simulation. In order to apply the rotation pairs of the front and back wheels of the wheelchair of the ADAMS and IF function and AZ function,many simulation experiments are carried out to simulate the parameters of the driving motor and the mechanical parameters of the mechanical legs. The mechanical characteristics of the key parts of the robot are compared. The kinematics curves and the mechanical curves are analyzed. And the stability of the climbing process is analyzed. It provides an important basis for reasonable selection of the model and the length of the machine,and provided a theoretical basis for the optimization design of other mechanisms.